Report of the Special Committee on Preferences on its ... session - United Nations Conference on Trade and Development (New York : United Nations, 1969)
This is a succinct account of the proceedings of the Special Committee on Preferences at its first session.
"TD/B."
"TD/B/AC."
osc 19/11/2018
Loans
Keywords: Tariff preferences; International cooperation; Commerce; International cooperation; Tariff preferences; Developing countries; Developing countries